A 4-year prospective study of the progression of periodontal disease in a rural Chinese population. Issue 2 (February 2015) - Pei, Xiyan; Ouyang, Xiangying; He, Lu; Cao, Caifang; Luan, Qingxian; Suda, Reiko
Abstract Objectives The natural progression of periodontitis in the Chinese population is not well researched. We investigated the progression of periodontal disease over 4 years in 15–44-year-old Chinese villagers with no access to regular dental care. Methods In 1992, 486 villagers were enrolled, and in 1996, 413 villagers were re-examined. Probing depth (PD) and clinical attachment level (CAL) were examined at six sites per tooth. Sites with ΔCAL ≥3 mm were defined as active sites. Cross-sectional and longitudinal analyses were performed using means and percentile plots. Results The mean CAL increased by 0.26 mm over 4 years. The incidence of periodontitis (at least one site with CAL ≥3 mm) was 8%. The incidence of periodontitis among those with no periodontal disease at baseline was 44.9%. Seventy-eight percent of the subjects had at least one active site. In the 15–24-year group, 244 of 401 active sites had gingival recession, while only 51 active sites had both gingival recession and deeper pockets. In the 25–34-year and 35–44-year groups, almost one-third of the active sites (329/1087) and more than one-third of the active sites (580/1312) respectively had a combination of gingival recession and deeper pockets. Conclusions In this study, we demonstrated that in Chinese population without regular dental care, both the initiation of periodontitis and progression of previously existed periodontitis contributed to the natural progression of periodontitis and periodontal pocketing played a greater role with age increasing. Clinical significance This rare study reports the natural progression of periodontal disease in a group of Chinese villagers (15–44 years) with virtually no access to regular dental care.